2013
DOI: 10.1017/s1431927613013640
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Reconstruction of Murine Peyer's Patches from Immunostained Cryosections

Abstract: Peyer's patches, macroscopic aggregates of lymphoid follicles present throughout the small intestines of humans and other mammals, are considered the gateway through which luminal dietary antigens and microbes are sampled by the mucosal immune system. The cellular make-up of Peyer's patch lymphoid follicles is not only complex, but highly dynamic, as there are at least four major cell types that are known to migrate in response to antigenic stimulation. In an effort to capture the complexity and dynamic nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…To test if there were changes in uptake of C. albicans by SED CD11c + DC stimulated with CT, we cogavaged C. albicans with CT and harvested PP after 4 h. The results revealed when compared to the control (Fig. 5A) that CT did in fact promote DC migration towards the FAE as previously reported [34,47]; however, CT did not affect sampling efficiency of C. albicans by SED DCs (Fig. 5B).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…To test if there were changes in uptake of C. albicans by SED CD11c + DC stimulated with CT, we cogavaged C. albicans with CT and harvested PP after 4 h. The results revealed when compared to the control (Fig. 5A) that CT did in fact promote DC migration towards the FAE as previously reported [34,47]; however, CT did not affect sampling efficiency of C. albicans by SED DCs (Fig. 5B).…”
Section: Resultssupporting
confidence: 62%
“…We and others had previously shown that the potent non-inflammatory mucosal adjuvant CT stimulates migration of DCs into the FAE [34,47,48]. To test if there were changes in uptake of C. albicans by SED CD11c + DC stimulated with CT, we cogavaged C. albicans with CT and harvested PP after 4 h. The results revealed when compared to the control (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…As the inductive sites of intestinal immunity, PPs are the primary sites through which particulate antigens and microbes are sampled (11). The microarchitecture of PPs is quite unique, as they are interspersed along the antimesenteric side of the ileum and can be seen with the naked eye as aggregate lymphoid structures (11, 12). Each PP contains multiple follicles that are individually equipped with an epithelial barrier called the follicle-associated epithelium (FAE).…”
Section: Introductionmentioning
confidence: 99%
“…Below the FAE in the sub-epithelial dome (SED), there is an extensive network of at least five subsets of mononuclear phagocytes and a B-cell-rich germinal center (GC) that also contains follicular dendritic cells flanked by T-cell-rich interfollicular regions. In concert, these cells all play an important role in sampling and immune surveillance (11, 13). Because PPs can be a very delicate and technically difficult tissue to work with, many gut models have used cell lines such as the Caco-2 and FaDu to understand sampling and transcytosis (14, 15).…”
Section: Introductionmentioning
confidence: 99%